2018
DOI: 10.1007/s00384-018-3025-7
|View full text |Cite
|
Sign up to set email alerts
|

Damage control surgery in perforated diverticulitis: ongoing peritonitis at second surgery predicts a worse outcome

Abstract: Ongoing peritonitis after DCS is a predictor of a worse outcome in patients with perforated diverticulitis. Enterococcal and fungal infections have a negative impact on occurrence of OP and overall outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 28 publications
2
17
0
5
Order By: Relevance
“…Several studies have addressed the intestinal continuity during surgical treatment for acute diverticulitis. There are three cohort studies and four randomized trials [116][117][118][119][140][141][142]. The randomized clinical trials all include a diverting loop ileostomy in the primary anastomosis arm.…”
Section: What Is the Role Of Restoration Of Intestinal Continuity Witmentioning
confidence: 99%
“…Several studies have addressed the intestinal continuity during surgical treatment for acute diverticulitis. There are three cohort studies and four randomized trials [116][117][118][119][140][141][142]. The randomized clinical trials all include a diverting loop ileostomy in the primary anastomosis arm.…”
Section: What Is the Role Of Restoration Of Intestinal Continuity Witmentioning
confidence: 99%
“…In a recent update of their results, Sohn et al 4 confirmed the benefits of DCS. However, in our opinion, an incorrect selection of patients persisted.…”
mentioning
confidence: 88%
“…Only 22% of DCS patients (16/74) met severe septic shock criteria. 4 We do not agree with the authors’ choice to subject the remaining non-septic population (78%; 58/74) to DCS, a complex surgical procedure for real emergency situations.…”
mentioning
confidence: 93%
See 2 more Smart Citations